COLLABORATIVE GOVERNANCE DALAM PROGRAM ONE VILLAGE ONE PRODUCT (OVOP) UNTUK MENINGKATKAN PADes DI KECAMATAN SUMEDANG SELATAN - Fitrianti, Sofia Nur (JRPA - Journal of Regional Public Administration, 2025)
This research aims to examine the implementation of Collaborative Governance within the OVOP Program, to identify the obstacles encountered, and to explore efforts made to overcome these challenges. The research involved informants from the OVOP Program as well as several stakeholders collaborating with the program, totaling 7 individuals. Data collection techniques included library research and field studies consisting of observation, interviews, and documentation. The data processing procedures in this study involved data reduction, data presentation, verification, and triangulation. The final results show that the implementation of Collaborative Governance within the One Village One Product (OVOP) Program to increase PADes in South Sumedang District can be considered fairly good overall. However, several issues were identified, including problems related to resources, knowledge, limited forums, supporting basic rules for collaboration, and face-to-face dialogue, which remains inadequate due to the lack of scheduled regular meetings among the stakeholders involved in the OVOP program. The obstacles faced include the need to change the mindset of OVOP business actors, ongoing miscommunication among stakeholders, unprofessional administration, inconsistencies between central and local government policies, and leaders who are indifferent and lack innovation, all of which hinder the development of the OVOP Program and the achievement of increased PADes. Efforts to overcome these challenges include changing the mindset of OVOP participants, establishing routine communication among stakeholders, and organizing training and workshops for leaders and stakeholders to foster innovation.